Erudición y temporalidad abolida. (Presencias de Petrarca en Secretum de A. Prieto) - Prado Biezma, Javier del (Cuadernos de Filología Italiana, 2005)
In Antonio Prieto’s novel, Secretum, due to its condition of a canzoniere in prose, the presence of the great Italian poet constitutes the key for both the text formal organization and the text thematic organization; there is a global pertrarchisation, in the facts superficial level as well as in the actanctial deep structure; the intertextual level is strictly petrarchist; in the metadiscoursive level a discourse about writing and life, which could have been perfectly Petrarch’s, is built and commented. In this article the author studies the function of quotes, which are not only mere support, but which achieve authentic ontological nature; the function of the title of the novel and its narrative voices are also studied.
Keywords: Humanism; temporality; existential erudition